Epidemiology a very short introduction - Saracci, Rodolfo, 1936- (Oxford : Oxford University Press, 2010)
Rodolfo Saracci dispels some of the myths surrounding the study of epidemiology. He provides a general explanation of the principles behind clinical trials and explains the nature of basic statistics concerning disease.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Epidemiology